Exploring Labor Migration Patterns: A Study On Uzbek Migrant Workers Abroad - Rikhsievna, Shayusupova Lobar; Ugli, Khasanov Azizjon Akhrol (Journal of Higher Education and Academic Advancement, 2024)
This study explores the various methods employed by labor migrants from Uzbekistan to migrate abroad for employment, both temporarily and permanently. It provides a comprehensive analysis based on data from a survey conducted by official sources. The research reveals the significant presence of Uzbek migrant workers in countries such as the Russian Federation, Kazakhstan, Turkiye, and Korea, with construction being the primary sector of employment. It also examines the role of the Foreign Labor Migration Agency (FLMA) in facilitating overseas employment and highlights Uzbekistan's efforts to diversify its labor migration destinations amidst growing concerns regarding migrants in Russia. The findings underscore the need for a comprehensive review incorporating data from both Uzbekistan and the receiving countries to understand the full scope of labor migration dynamics.